Effective Sexual Education Model For Preventing Sexual Violence in Children - Sipahutar, Ida Erni; Hartati, Ni Nyoman; Runiari, Ni Nengah; Wedri, Ni Made; Suardani, Ni Luh Ketut; Armynia Subratha, Hesteria Friska (Babali Publisher, 2024)
Introduction: Children are vulnerable to sexual abuse because they are physically weak and cannot defend themselves. Threats to withhold reporting occurrences also frighten people. Sexual violence is usually done by family, neighbors, or relatives. The study aimed to investigate the effectiveness of developing a sexual health education model toward the knowledge and attitude of mothers.Methods: The research method used Quasi-Experimental with nonequivalent Control Group Design. A total of 60 mothers were divided into education and control groups. Knowledge and attitude questionnaires were used. T-test and Wilcoxon Signed Rank Test were used to analyze the difference between the pre-post test within group.Results: The study found that 33 respondents (55%) in the pre-test treatment group had a low knowledge level, and 44 respondents (73.3%) in the post-test treatment group (p = 0.001). The attitude of the respondents in the pre-test treatment group showed that most were poor, 60 respondents (100%), and 31 respondents (51.7%) in the post-test treatment group were poor (0.073). Most of the respondents in the pre-test control group had a low knowledge level of 32 respondents (53.3%), and the post-test control group had a high level of knowledge of 31 respondents (52.1%) (p= 0.000). Most respondents in the pre-test control group had a poor attitude, with 34 respondents (56.7%), and the post-test control group had a good attitude, with 33 respondents (55%) (p = 0.000).Conclusion: The module on sexual development education for children cannot affect people's views on teaching children sexual development.